A generalization of the second Pappus–Guldin theorem - Harald Schmid (Results in Applied Mathematics)
This paper deals with the question of how to calculate the volume of a body in R3 when it is cut into slices perpendicular to a given curve. The answer is provided by a formula that can be considered as a generalized version of the second Pappus–Guldin theorem. It turns out that the computation becomes very simple if the curve passes directly through the centroids of the perpendicular cross-sections. In this context, the question arises whether a curve with this centroid property exists. We investigate this problem for a convex body K by using the volume distance and certain features of the so-called floating bodies of K. As an example, we further determine the non-trivial centroid curves of a triaxial ellipsoid, and finally we apply our results to derive a rather simple formula for determining the centroid of a bent rod.